Novel recursive partitioning analysis classification for newly diagnosed glioblastoma: A multi-institutional study highlighting the MGMT promoter methylation and IDH1 gene mutation status. Issue 1 (April 2017) - Wee, Chan Woo; Kim, Eunji; Kim, Nalee; Kim, In Ah; Kim, Tae Min; Kim, Yu Jung; Park, Chul-Kee; Kim, Jin Wook; Kim, Chae-Yong; Choi, Seung Hong; Kim, Jae Hyoung; Park, Sung-Hye; et al.
Abstract: Background and purpose: To refine the recursive partitioning analysis (RPA) classification for glioblastoma incorporating the MGMT methylation and IDH1 mutation status. Methods and Materials: Three-hundred forty patients were treated with radiotherapy plus concurrent and adjuvant temozolomide in three tertiary-referral hospitals. MGMT methylation and IDH1 mutation status were available in all patients. Methylation of the MGMT ( MGMT meth) and mutation of IDH1 ( IDH1 mut) were observed in 42.4% and 6.2% of the patients, respectively. Results: The median follow-up for survivors and all patients was 33.2 and 20.5 months, respectively. The median survival (MS) was 23.6 months. RPA was performed on behalf of the results of the Cox proportional hazards model. MGMT methylation generated the initial partition ( MGMT meth vs. MGMT unmeth) in the RPA. Three final RPA classes were identified; class I = MGMT meth/ IDH1 mut or MGMT meth/ IDH1 wt/GTR/KPS ≥ 90 (MS, 67.2 months); class II = MGMT meth/ IDH1 wt/GTR/KPS < 90, MGMT meth/ IDH1 wt/residual disease, MGMT unmeth/age < 50, or MGMT unmeth/age ≥ 50/GTR (MS, 24.0 months); class III = MGMT unmeth/age ≥ 50/residual disease (MS, 15.2 months). Conclusions: A novel RPA classification for glioblastoma was formulated highlighting the impact of MGMT meth and IDH1 mut in the temozolomide era. This model integrating pertinent molecular information can be used effectively for the patient stratification in future clinical trials. An external validation is ongoing.